Perbedaan Kreativitas Remaja Ditinjau dari Peran Seks Androgini dan Non-Androgini - Rismar Julia Utami (Consilium : Berkala Kajian Konseling dan Ilmu Keagamaan, 2020)
The study aims to determine the difference in adolescents ' creativity is reviewed from the role of androgynous and non-androgynous sex. This research uses quantitative methods. The research Data is obtained from sex role scale (BSRI) and Figural test of type B sub Test 3 (circle). The sample in this research is the students of XI SMA Negeri 4 Sungai Penuh. The number of samples in this study was 84 people. The results showed that there was no difference between the creativity of teenagers who had androgynous sex roles and teenagers who had non-androgynous sex roles (P = 0646, p > 0.05).  From the results of this study can be concluded that in addition to the sex role factors, psychological safety factor and psychological Freedom factor also determines the development of individual creativity.